Physicochemical and Microbiological Quality of Holy Waters in the Kathmandu Valley - Nakarmi, Niraj; Karki, Sabi; Shrestha, Sony (SXC Journal, 2026)
Holy water sources are regarded by many people as pure and sacred. People use these waters for various devotional activities, like bathing, sprinkling, drinking and others. As people come in direct contact with these waters, such waters should be of good quality in order to protect the devotee’s health. As these sources are open or are flowing, they are vulnerable to contamination from environmental pollutants and human and animal activities. This study was carried out to evaluate the physicochemical and microbiological quality of holy waters used in Kathmandu Valley. The samples were collected aseptically in sterile and clean glass bottles and were analyzed using the standard procedures outlined in Standard Methods for the Examination of Water and Wastewater (2017) published by the American Public Health Association. All the physicochemical parameters tested were within the limits (pH 6.56, TDS 187.25 mg/l, conductivity 259.88 μS/cm, chloride 23.4 mg/l, hardness 33.25 mg/l, iron 0.03 mg/l, ammonia 0.16 mg/l) of the requirements of National Drinking Water Quality Standards, 2005 except for nitrate (31.75 mg/l). In contrast, microbiological analysis showed high coliform counts (5.114 log10 CFU/ml). Moreover, the presence of multidrug resistant E. coli in 50% of the samples suggests high risk for the devotees from various water borne diseases. Overall, the findings indicate that although these holy water sources hold great religious and cultural significance, their sanitary condition requires attention. Proper sanitation, regular monitoring, and improved hygiene practices are necessary to ensure the safety of people using these waters.